The impact of soil warming on fine root trait responses of trees, deciduous vs. coniferous: a meta-analysis - Rezapour Azadeh; Labbafi Mohammadreza; Oja Tõnu (Metsanduslikud Uurimused, 2022)
We compiled data from 149 paired observations from 43 publications and performed a meta-analysis to evaluate the variability of trees’ fine root trait responses under various global soil warming experiments. The impacts of warming magnitude, soil depth, and different tree species (deciduous vs. coniferous), on the responses of fine root biomass (FRB), and fine root morphology were assessed in this study. Our results confirmed that soil warming increased FRB while having no significant effect on fine root morphological traits, such as specific root length (SRL), specific root area (SRA), and diameter (D). The effect of warming on FRB decreased significantly at higher warming magnitude. The effect of tree species was also evident in the response of FRB to soil warming magnitude. Furthermore, warming effects on SRA and D increased in deeper soil horizons. The present meta-analysis provides an improved understanding of trees’ fine roots and the tree species-specific adaptive strategy under future soil warming episodes. Our results suggest that trees will resist the altering soil warming conditions by modifications more in fine root biomass allocation rather than morphological adjustments.